Extensive diversity of intestinal trichomonads of non-human primates - Smejkalová, Pavla; Petrželková, Klára J; Pomajbíková, Kateřina; Modrý, David; Čepička, Ivan (Parasitology, 2012)
Despite the fact that the non-human primates are our closest relatives and represent a species-rich mammalian group, little is known about their intestinal protistan parasites/commensals. Particularly, the intestinal trichomonads represent a neglected part of the fauna of the primate digestive system. We have established 30 trichomonad strains isolated from feces of 11 primate species kept in 3 Czech zoos and performed an analysis of their SSU rDNA and ITS1-5·8S rDNA-ITS2. Our results showed that intestinal trichomonads are rather common among non-human primates. Molecular phylogenetic analysis showed that the strains are unexpectedly diversified, belonging to 8 or 9 distinct species. Interestingly, the vast majority of the strains from non-human primates belonged to the genus Tetratrichomonas while no member of this genus has been found in the human intestine so far. In addition, hominoid and non-hominoid primates differed in their intestinal trichomonads. Our results suggest that captive primates possibly may be infected by intestinal trichomonads of other vertebrates such as pigs, cattle, birds, tortoises and lizards.
Keywords: mezerníky ribozomální DNA; DNA, Ribosomal; Phylogeny; Primate Diseases; protozoální DNA; DNA, Protozoan; primáti; Intestinal Diseases, Parasitic; zvířata; nemoci primátů; biodiverzita; fylogeneze; ribozomální DNA; Trichomonadida; Animals; DNA, Ribosomal Spacer; Primates; parazitární nemoci střev; Biodiversity